2009
DOI: 10.1213/ane.0b013e318195e11d
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Postmortem Findings in 235 Surgical Intensive Care Patients with Sepsis

Abstract: Relevant postmortem findings explaining death in surgical ICU patients who died because of sepsis/septic shock were a continuous septic focus in approximately 80% and cardiac pathologies in 50%. The most frequently affected organs were the lungs, abdomen, and urogenital tract. More diagnostic, therapeutic and scientific efforts should be launched to identify and control the infectious focus in patients with sepsis and septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
148
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(161 citation statements)
references
References 21 publications
6
148
0
7
Order By: Relevance
“…As known, lung tissue damage is observed in 90% of patients dying from sepsis and its associated complication (40). The histopathological features of lung injury in septic mice demonstrated here are resembled in the clinical condition of patients with sepsis (41).…”
Section: R E S E a R C H A R T I C L Esupporting
confidence: 67%
“…As known, lung tissue damage is observed in 90% of patients dying from sepsis and its associated complication (40). The histopathological features of lung injury in septic mice demonstrated here are resembled in the clinical condition of patients with sepsis (41).…”
Section: R E S E a R C H A R T I C L Esupporting
confidence: 67%
“…Interestingly, post-mortem findings in surgical ICU patients who died from sepsis or septic shock revealed that in the majority of cases, a septic focus was still detectable even after treatment duration of 7 days (10). Histological analyses further confirmed a high rate of undetected or nonadequately addressed pulmonary or abdominal foci (10,11). Thus, the continuing presence of a pathologic trigger might contribute to the dramatic disease progress, leading to organ failure and death in these critically ill patients (12).…”
Section: Immunologic Dysfunctions Contribute To the High Mortalitymentioning
confidence: 80%
“…One of the clinical manifestation of sepsis is the impairment and insufficiency of cardiac function. A previous study indicated that, among 235 patients who succumbed to sepsis or septic shock-associated mortality, those exhibiting cardiovascular system failure accounted for 35.3% (5). As the inflammatory reaction is important in sepsis, previous studies have attempted to use monoclonal antibodies raised against specific inflammatory factor receptors to inhibit the inflammatory reaction (2,6).…”
Section: Introductionmentioning
confidence: 99%